PENGGUNAAN PERANGKAT MOBILE TERHADAP SUATU TINDAK KEJAHATAN (STUDI KASUS PADA TEMUAN BUKTI DIGITAL SHORT MESSAGE SERVICE (SMS) DI UNALLOCATED DATA) - Tommy Nugraha Manoppo (Cyber Security dan Forensik Digital, 2019)
Mobile devices usage has become a part of daily life modern humans today. And one of mobile devices that is almost owned by mobile devices users is mobile phone, including a smartphones. As an electronic devices that can store data, even various kinds of data types, that information stored from data on mobile phone can reflect the user’s activity. So the information can be described as a chronologically if needed. In this study, there are case studies about findings and handlings of digital evidence form of Short Message Services (SMS) that obtained on unallocated data in an android smartphone. By practically testing the procedures, the results show that steps and stages used for handling mobile devices evidence could be run dynamically, in the sense that, there are several procedural steps can be run as simultaneously, but the activity stages could be run regularly too. So the artefacts  has a forensically sound elements and can be proven as a scientific with the clear stages.